Thirty Years of World Music. (3rd February 2015) - Taylor, Timothy
Abstract : This article tracks major developments in world music since the inception of the term in the late 1980s, situating the rise and continued currency of world music as an effect of the most recent phase of globalization in the west, which itself is part of the neoliberal capitalism of the past few decades.